Effect Of Unsaturated Fatty Acid Omega-3 On Some Histological Criteria In White New Zealand Rabbits Administrated With Cyclosporine Drug - Jawad, Murtadha M.; Al-Kraity, Wijdan Rajh Hamza (Medical Science Journal for Advance Research, 2021)
The present study was aimed efficiency to evaluate the unsaturated fatty acid omega-3 in reducing the side effects that resulted from administration of cyclosporine drug in white New Zealand rabbits. (60) from white males’ rabbits were used in this study, the animals divided into major four groups (15) rabbits per group and its subdivision into three groups (5) rabbits per group. The first group is orally administered with normal saline, second groups were administered cyclosporine (25mg/kg) only. Third groups were administered cyclosporine (25mg/kg) in the first day and Omega-3 (500mg/kg) in the second day, while Fourth groups were administered cyclosporine (25mg/kg) in the first day and omega-3 (1000mg/kg) in the second day for periods (21,30,60) days respectively. After ending study periods, the animals were sacrificed and the blood was collected and samples from liver were taken and the results were showed the following: the histological study showed pathological changes after administration of cyclosporine (25mg/kg) with blood congestion for period (21day), while severe blood congestion with beginning of fibrosis for period (30day) while in the period (60day) very severe blood congestion with aggregation of inflammatory cells and grow of fibroblast cells were showed. while the interaction between cyclosporine and two concentrations (500&1000mg/kg) of omega-3 were showed non-pathological changes in liver tissues. From this study concluded that omega-3 have an important role in the reducing histopathology side effects that result from administration of cyclosporine drug in white rabbits.